ANALISIS PERILAKU SISWA DI LINGKUNGAN SEKOLAH KELAS XI SMA ADABIAH 2 PADANG - Rinda Sutra; Wibi Wijaya; Yanti Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of student discipline at Adabiah 2 High School in Padang, characterized by lateness to school, incomplete attributes, truancy, and unexcused absences (alpha). This indiscipline negatively impacts student academic achievement, the learning process, and the classroom atmosphere. The purpose of this study is to analyze the behavior of eleventh-grade students, particularly in grades XI Phase 4 and XI Phase 9, in relation to forms of school discipline violations. The study used a descriptive qualitative method with data collection techniques through observation, interviews, and document studies. Informants were selected purposively, consisting of homeroom teachers, guidance counselors, and students. Data were analyzed using the Miles and Huberman model through the stages of collection, reduction, presentation, and drawing conclusions. The results showed that student tardiness was generally influenced by internal factors such as the habit of playing with gadgets until late at night and lack of parental control. Incomplete attributes were caused by low awareness of school rules, while truancy and alpha behavior were related to low learning motivation and the influence of the social environment. The impact of this behavior not only decreases learning outcomes but also disrupts the effectiveness of learning and the classroom atmosphere. This research emphasizes the important role of teachers, parents, and schools in instilling discipline and creating a conducive learning environment. Keywords: Student behavior, school discipline, Adabiah 2 High School, Padang